2015
DOI: 10.1007/s00894-015-2595-3
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport properties of BN sheet on adsorption of ammonia (NH3) gas

Abstract: We report the detection of ammonia gas through electronic and transport properties analysis of boron nitride sheet. The density functional theory (DFT) based ab initio approach has been used to calculate the electronic and transport properties of BN sheet in presence of ammonia gas. Analysis confirms that the band gap of the sheet increases due to presence of ammonia. Out of different positions, the bridge site is the most favorable position for adsorption of ammonia and the mechanism of interaction falls betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In this quest different nanostructres are successfully explored to various toxic gases [27][28][29][30][31][32][33][34][35]. Sensitivity of black phoespheren for NH 3 and NO 2 have been checked out both for finite and periodic system.…”
Section: Black-phospherene As Nh 3 and No 2 Sensormentioning
confidence: 99%
“…In this quest different nanostructres are successfully explored to various toxic gases [27][28][29][30][31][32][33][34][35]. Sensitivity of black phoespheren for NH 3 and NO 2 have been checked out both for finite and periodic system.…”
Section: Black-phospherene As Nh 3 and No 2 Sensormentioning
confidence: 99%
“…Identifying these signaling metabolites (disease markers) and measuring them in trace concentrations is not a trivial problem, and the low concentrations of analyte molecules presents a major challenge, along with the specificity to a given analyte. Recently, low-dimensional materials used for gas detection has become a trend [3, 4], it has been reported that it is possible to use graphene as a gas sensor with high sensitivity and high accuracy for detecting ammonia groups [5, 6]. Graphene is considered to be an excellent kind of sensor material due to its following properties: (i) graphene is a single atomic layer of graphite with a larger specific area than any other materials, which maximizes the interaction between the surface dopants and the adsorbates; (ii) as a kind of special material with zero bandgap, graphene has a extremely low Johnson noise [7], for which a slight change of carrier concentration can cause a notable variation of electrical conductivity; (iii) graphene has limited crystal defects, which ensures a low level of excess noise caused by thermal switching [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the DFT calculations, the adsorption energy of the adsorbed NH 3 molecule on B/N/C atoms is equal to 0.112 eV, 0.4 eV, and 0.48 eV, respectively. 29,34 For molecules with neglected interactions (far from the ribbon's surface), the adsorption probability weight depends on the ribbon's area. For the NH 3 molecules sufficiently close to the ribbon area, the adsorption probability weight is different for B/N/ C atoms.…”
Section: 29-31mentioning
confidence: 99%
“…The intensity of HOMO state increases by NH 3 adsorption. 29 In the A 9 BNNR, for both cases with different concentration, the modifications of electronic properties in higher and lower energies are neglected. Figure 8 shows DOS of A 9 BNNR-A 7 GNR system in the presence of gas adsorption.…”
Section: Density Of Statesmentioning
confidence: 99%